CUSTOMER DATA SEGMENTATION ON TOP 3 ONLINE FOOD ORDERING APPLICATIONS TO MEMBERS OF ROLLER SKATES COMMUNITY IN JAKARTA USING K-MEANS CLUSTERING METHOD - Anastasia Della Resti; Jerry Heikal (Jurnal Scientia, 2023)
Advances in technology have made it easier for users to be able to do various things things only by using smartphone devices, one of which is ordering food through applications on smartphones. The purpose of this study is to identify customer characteristics, product categories and merchant categories in the top 3 online food ordering applications in Jakarta using the K-Means Clustering method. There are three variables, namely customer characteristics, product categories and merchant categories. Data processing is assisted by using the SPSS V. 25 application. Loyal customers of GoFood are cluster 2. In addition, GoFood also has loyal customers in cluster 3. Loyal customers of GrabFood are cluster 4. In addition, GrabFood also has loyal customers in cluster 5. Loyal customers of ShopeeFood are cluster 1. In addition, ShopeeFood also has loyal customers in clusters 3.